Meningkatkan Kreativitas Guru Melalui Pelatihan Pembuatan Aplikasi Sederhana Berbasis Canva Web Prototype - Muhammad Idris Effendi; Radeni Sukma Indra Dewi; Lailatul Nurjanah; Bunga Ayu Dibtasari; Fierda Nursitasari Amaliya (I-Com: Indonesian Community Journal, 2024)
The rapid development of information and communication technology (ICT) has significantly transformed various aspects of life, including education. Utilizing technology in teaching processes enables the creation of more innovative, interactive, and flexible methods that can capture students' interest and enhance learning effectiveness. One such tool is Canva, a web-based graphic design platform that allows teachers to create engaging educational media, such as presentations, infographics, and simple web prototypes. Despite the availability of these technologies, many teachers still rely on conventional methods, which often fail to engage students accustomed to digital tools. This service program aimed to address this issue by providing training on creating simple web applications using Canva for Education. The training effectively improved teachers' skills in developing interactive and engaging learning materials, with 93% of participants successfully creating web-based media. This outcome underscores the importance of integrating modern technology into education to foster a dynamic and engaging learning environment